Translation of Children’s Speech in Frank Schaeffer’s Portofino - Czarnecka, Mira (Studia Anglica Posnaniensia, 2021)
The theme of the article is a research into the issue of translation of children’s speech. The analysis will be conducted based on three excerpts from a novel – Portofino – written by a contemporary American writer Frank Schaeffer and translated into Polish by the author of the article, early in her career as a translator. First, the results of text typology investigation by Anna Trosborg (1997b), Paul Kussmaul (1995, 1997) and Christiane Nord (2018) regarding cognitive structuring, text structures, and general style conventions will be highlighted. Then the outcomes of the translation process research (TPR) on cohesive aspects and structuring by Michael Carl, Srinivas Bangalore & Moritz Schaeffer (2016) will be summarised. This will be followed by the discussion of findings of Paul Thompson & Alison Sealey (2007), Gillian Lathey (2011), and Anna Čermáková (2018) regarding the issue of repetition and the aspects of point of view. Subsequently, the notion of style in a work of fiction will be introduced and followed by the description of stylistic and linguistic means used to achieve it. This will include the discussion of speech and thought presentation (STP) scales proposed first by Geoffrey Leech & Mick Short (2007) and then developed by Mick Short in cooperation with Elena Semino (2004). Next, the stylistic features of children’s speech and its linguistic exponents will be outlined. The translation analysis will focus on stylistic and linguistic devices used by the author to imitate children’s speech in the source text and their rendering by the translator in the target text. The achieved effect and translation equivalence will be evaluated, possible reasons behind any loss in meaning will become identified and some final recommendations for translators will get defined.